Exosome-driven transfer of tumor-associated Pioneer Translation Products (TA-PTPs) for the MHC class I cross-presentation pathway. (1st September 2016) - Duvallet, Emilie; Boulpicante, Mathilde; Yamazaki, Takahiro; Daskalogianni, Chrysoula; Prado Martins, Rodrigo; Baconnais, Sonia; Manoury, Bénédicte; Fahraeus, Robin; Apcher, Sébastien
ABSTRACT: Cellular immune reactions against non-self-epitopes require activation of cytotoxic CD8 + T-cells via cross-presentation of MHC class I-restricted peptides by professional antigen presenting cells (pAPCs), with the consequent detection and elimination of cells expressing the same antigens via the endogenous (direct) pathway. The source of peptides for the endogenous pathway is constituted of alternative mRNA translation products; however, it is still unclear which source of peptides is used for cross-presentation. Furthermore, the presentation of non-canonical translation products, produced during a non-conventional translation event, on class I molecules of tumor cells has been reported but how these peptides are generated, presented to pAPCs, and their capacity to stimulate CD8 + T cells is still not known. Here, we report that pioneer translation peptides (PTPs) derived from intron or exon pre-mRNAs can serve as tumor-associated antigens (TA-PTPs) and are delivered from the producing tumor cells to pAPCs via exosomes where they are processed by the cytosolic pathway. Injection of TA-PTPs and tumor-derived exosomes efficiently induce CD8 + T-cell proliferation and prevent tumor growth in mice. Our results show that TA-PTPs represent an efficient source of antigenic peptides for CD8 + T cell activation and that full-length proteins are not required for cross-presentation. These findings can have interesting implications for generating tolerance and for designing vectors to generate vaccines.